If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -3 = 17 + 9x Reorder the terms: -3 + -1x = 17 + 9x Solving -3 + -1x = 17 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + -1x + -9x = 17 + 9x + -9x Combine like terms: -1x + -9x = -10x -3 + -10x = 17 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -10x = 17 + 0 -3 + -10x = 17 Add '3' to each side of the equation. -3 + 3 + -10x = 17 + 3 Combine like terms: -3 + 3 = 0 0 + -10x = 17 + 3 -10x = 17 + 3 Combine like terms: 17 + 3 = 20 -10x = 20 Divide each side by '-10'. x = -2 Simplifying x = -2
| 7x-(4x-13)=40 | | 27/63 | | 3(2x-5)=44x-7 | | x+x+23+(x+23)/4=562 | | 4(4x-3)-6x=4(2x+3)-24 | | -20+2x=-12 | | -8x+9x=-1+7 | | -4(1+2r)-r=7(-r-4) | | 4(4x-3)-6x=4x+2(3x-6) | | x+25+4x=-34-4x-40 | | 6x+20+2x+4=90 | | 3x+3=4x+9 | | 6x+20+2x+4= | | 3(x-8)+x=4(x-7)+4 | | 25-(x+3)=2(2x+1) | | -5(m+1)-1=8m-7(7m+6) | | -150+5x=-4x+84 | | 2x-5=2x+6 | | 4x+10=6x-4 | | (8-10x*5x+4)=0 | | 5(6)+5(2)=5(6+2) | | 2(3x+1)=6x | | 21/48 | | X^2=3177 | | -24v^8-11v^6= | | 4/6m+5=12 | | -86+x=3 | | -12k^7+4k^8= | | 2y+3xy-8=5y+6 | | 4x-35=2x+41 | | -72=3d-11d | | 3x-15+2x+18=15 |